Posouzení informačního systému firmy a návrh změn - Hartman, Martin (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2014)
Diplomová práce se zabývá zhodnocením aktuálního stavu informačního systému vybrané firmy (působící v oblasti prodeje aut) a návrhu změn, které by vedly k odstranění zjištěných nedostatků. Při zhodnocení skutečného stavu systému bude použit průzkum pomocí dotazníku (metodika B2EPUS), analýzy HOS8 a SWOT.

The diploma thesis deals with the assessment of the current status of information system in the selected firm ( operating in the area of car sales ) and a proposal of changes that would lead to the removal of the identified deficiencies. In the assessment of the current status will be used to survey using a questionnaire (methodology B2EPUS), analysis HOS8 and SWOT.
Information System Assessment and Proposal for ICT Modification
Keywords: Informační systém; dotazník; metodika B2EPUS; analýza HOS8; analýza SWOT.; Information system; questionnaire; methodology B2EPUS; analysis HOS8; analysis SWOT.